Oxidative Stress Promotes Doxorubicin-Induced Pgp and BCRP Expression in Colon Cancer Cells Under Hypoxic Conditions (2017)
P-glycoprotein (Pgp) and breast cancer resistance protein (BCRP) are ATP binding cassette (ABC) transporters that are overexpressed in different drug-resistant cancer cell lines. In this study, we investigated whether doxorubicin promotes Pgp and/or BCRP expression to induce drug resistance in colon cancer cells under hypoxic conditions. We analyzed HIF-1? activity via ELISA, Pgp, and BCRP expression by qRT-PCR and the relationship between doxorubicin uptake and ABC transporter expression via confocal microscopy in HT-29WT and HT-29 doxorubicin-resistant colon cancer cells (HT-29DxR). These cells were treated with doxorubicin and/or CoCl2 (chemical hypoxia), and reactive oxygen species inductors. We found that the combination of chemically induced hypoxia and doxorubicin promoted Pgp mRNA expression within 24 h in HT-29WT and HT-29DxR cells. Both doxorubicin and CoCl2 alone or in combination induced Pgp and BCRP expression, as demonstrated via confocal microscopy in each of the above two cell lines. Thus, we surmised that Pgp and BCRP expression may result from synergistic effects exerted by the combination of doxorubicin-induced ROS production and HIF-1? activity under hypoxic conditions. However, HIF-1? activity disruption via the administration of E3330, an APE-1 inhibitor, downregulated Pgp expression and increased doxorubicin delivery to HT-29 cells, where it served as a substrate for Pgp, indicating the existence of an indirect relationship between Pgp expression and doxorubicin accumulation. Thus, we concluded that Pgp and BCRP expression can be regulated via cross-talk between doxorubicin and hypoxia, promoting drug resistance in HT-29 WT, and HT-29DxR cells and that this process may be ROS dependent. J. Cell. Biochem. 118: 1868–1878, 2017. © 2017 Wiley Periodicals, Inc. © 2017 Wiley Periodicals, Inc.